Kewarganegaraan dan Geopolitik: Membangun Kesadaran Nasional di Era Global - Rani, Indri Mustika; Rezeki, Ayu Sri; Nazla, Nazla; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This article examines in depth the relationship between the concepts of citizenship and geopolitics in the face of the increasingly complex challenges of globalization. The main objective of this article is to encourage the development of national awareness through the integration of geopolitical approaches in civic education. In the context of developing countries such as Indonesia, citizenship education not only serves to form law-abiding citizens, but also as a strategic means to instill national values and national identity. According to Kymlicka (2001), citizenship education plays a role as the main foundation in strengthening solidarity and identity in a nation-state. Therefore, understanding geopolitical dynamics is an important part of fostering an understanding of Indonesia's strategic position in the regional and global region. This article emphasizes that the geopolitical approach can help students in developing national insights that are contextual and relevant to current issues. The research was conducted using a literature study method and a qualitative approach that allowed an in-depth exploration of previous theories and findings. The results of the study show that civic education integrated with a geopolitical perspective is able to increase the love of the homeland and the active participation of citizens in maintaining the integrity of the nation. Furthermore, this article finds that the integration between civic education and geopolitics can be a strong foundation in fortifying the younger generation from the negative influences of globalization that can erode national values. Knowledge of geopolitics provides students with a thorough understanding of the challenges and opportunities facing Indonesia in international relations. Civic education with a geopolitical approach also strengthens students' socio-political intelligence in responding to various contemporary issues, such as regional conflicts, energy security, and the influence of global powers on national sovereignty. In this case, teachers have a strategic role as facilitators to instill a contextual and applicative understanding of geopolitics. This study recommends the need to reformulate the civic education curriculum in order to be able to respond to the needs of the times and strengthen geopolitical awareness from an early age. Thus, students not only become cognitively intelligent citizens, but also have social sensitivity, national responsibility, and commitment to the integrity of the nation and state. The article also emphasizes that global challenges require an educational response that is adaptive, visionary, and based on national contexts. In conclusion, the integration of civic education and geopolitical insight is an important step in forming a resilient generation of nations in the global era.